2006
DOI: 10.1385/endo:29:3:457
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Islet Function in ω3 Fatty Acid-Depleted Rats: Glucose Metabolism and Nutrient-Stimulated Insulin Release

Abstract: In order to gain information on the determinism of the perturbation of fuel homeostasis in situations characterized by a depletion in long-chain polyunsaturated omega3 fatty acids (omega3), the metabolic and hormonal status of omega3-depleted rats (second generation) was examined. When required, these rats were injected intravenously 120 min before sacrifice with a novel medium-chain triglyceride-fish oil emulsion able to provoke a rapid and sustained increase of the omega3 content in cell phospholipids. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 17 publications
10
62
0
3
Order By: Relevance
“…It has been reported that the lipid fraction of O. ficus-indica seed oil contains polyunsaturated fatty acids (linoleic acid) and monounsaturated fatty acids (oleic acid), and the unsaponifiable fraction contains liposoluble vitamins (tocopherols, vitamin K1), sterols, and carotenoids (b-carotene) (Ennouri et al, 2005;Mannoubi et al, 2009;Oguzhan et al, 2006;Ramadan & Morsel, 2003). The omega-3 fatty acids increase the insulin secretion stimulated by D-glucose by contact with Langerhans islet beta cells (Oguzhan et al, 2006). In addition, polyunsaturated fatty acids enhance cell membrane fluidity and GLUT4 transporter expression (Manco et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the lipid fraction of O. ficus-indica seed oil contains polyunsaturated fatty acids (linoleic acid) and monounsaturated fatty acids (oleic acid), and the unsaponifiable fraction contains liposoluble vitamins (tocopherols, vitamin K1), sterols, and carotenoids (b-carotene) (Ennouri et al, 2005;Mannoubi et al, 2009;Oguzhan et al, 2006;Ramadan & Morsel, 2003). The omega-3 fatty acids increase the insulin secretion stimulated by D-glucose by contact with Langerhans islet beta cells (Oguzhan et al, 2006). In addition, polyunsaturated fatty acids enhance cell membrane fluidity and GLUT4 transporter expression (Manco et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure used to prepare second generation ω3-depleted rats and the diet offered to these rats were defined in a prior report (3). Some of these rats were injected intravenously 60 min before sacrifice with 1.0 ml of either an ω3 fatty acid-rich medium-chain triglyceride:fish oil emulsion (MCT:FO) or a control ω3 fatty acid-poor medium-chain triglyceride:olive oil emulsion (MCT:OO) (3).…”
Section: Methodsmentioning
confidence: 99%
“…Taken as a whole, these results suggest that, in the (Fsal) rats, a modest improvement of insulin sensitivity was opposed, in terms of glucose homeostasis, by a decreased secretory response of insulin-producing cells to a rise in plasma D-glucose concentration. The latter situation is reminiscent of that recorded in isolated pancreatic islets, when comparing the insulinotropic action of several secretagogues in islets from 2nd generation ω3-depleted rats to that of control animals both exposed to diets not enriched with D-fructose, the output of insulin being higher in the ω3-depleted rats than in the control animals (11,12).…”
Section: Discussionmentioning
confidence: 75%